2017
DOI: 10.1073/pnas.1700790114
|View full text |Cite
|
Sign up to set email alerts
|

Thermal combination therapies for local drug delivery by magnetic resonance-guided high-intensity focused ultrasound

Abstract: Several thermal-therapy strategies such as thermal ablation, hyperthermia-triggered drug delivery from temperature-sensitive liposomes (TSLs), and combinations of the above were investigated in a rhabdomyosarcoma rat tumor model ( = 113). Magnetic resonance-guided high-intensity focused ultrasound (MR-HIFU) was used as a noninvasive heating device with precise temperature control for image-guided drug delivery. For the latter, TSLs were prepared, coencapsulating doxorubicin (dox) and [Gd(HPDO3A)(HO)], and inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 68 publications
(85 reference statements)
4
60
0
Order By: Relevance
“…In recent studies using doxorubicin TSLs, FUS ablation was suggested as a new strategy to be combined with drug delivery systems (thermosensitive or not) [31,69]. Both presented studies show an impressive efficacy of this method of FUS treatments (ablation / hyperthermia) in combination with thermosensitive liposomes.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
See 1 more Smart Citation
“…In recent studies using doxorubicin TSLs, FUS ablation was suggested as a new strategy to be combined with drug delivery systems (thermosensitive or not) [31,69]. Both presented studies show an impressive efficacy of this method of FUS treatments (ablation / hyperthermia) in combination with thermosensitive liposomes.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…followed by ablation showed the best therapeutic outcome compared with other treatments. This appeared to be due to direct induction of thermal necrosis in the tumour core and efficient drug delivery to the surrounding rim [31].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…thermosensitive liposome infusion during MRI-HIFU light hyperthermia reduced tumor growth compared to tumors treated with liposome without hyperthermia [108]. Hijnen et al, also investigated the use of MRI-HIFU with the intravascular release of DOX encapsulated in TSLs in a preclinical setting using a rhabdomyosarcoma mouse tumor model [109]. All HIFU heating strategies combined with TSL resulted in increased DOX cell uptake in the interstitial space and a significant increase in drug concentrations in the tumor compared to a free DOX treatment [109].…”
Section: Mri-guided Thermometry: a Strategy For Real-time Monitoring mentioning
confidence: 99%
“…Recently, HIFU has been widely used in benign and malignant tumors such as uterine broids, breast cancer, liver cancer, pancreatic cancer, bone tumors, and kidney cancer [11]. Previous studies have suggested that magnetic resonance-guided high-intensity focused ultrasound (MR-HIFU) has the great potential for localized heat-mediated drug delivery of temperature-sensitive liposomes (TSL), which affects drug uptake and distribution [12].…”
Section: Introductionmentioning
confidence: 99%